Re- Positioning Research in Turbulent Times: Embracing Change in Innovation Science, Technology, Education and Business Perspectives. - Onderi, Henry L.N. (JRHSM, 2023)
The world is currently experiencing times of turbulence, occasioned by the Covid-19 pandemic and this has created disruption across economic sectors including education and business. This came with major disruptions and disorder across the sectors hampering economic growth and development while in some sense it brought restructuring and shifting of economic systems and a new world order. However, there has been witnessed transformation in terms of the virtual world development to cope with the rapidly emerging new normal and this has seen new innovations and emerging trends in science, technology, education and business among other economic sectors. Studies have shown that so far there is relatively low impact of innovation, science and technology in transforming education and business norms and practices especially in low-income countries. As such, there is need to integrate important aspects of science, technology and innovation (STI) into education and business systems because they have played a key role in responding to the COVID-19 pandemic and are essential for effective response to and recovery from the pandemic effects in low and middle-income settings and the unprecedented socio-economic crisis it has triggered. Re-thinking of an inclusive and empowering approach should become part of the mainstream across the sectors, both as a means of addressing the urgent turbulence and instabilities and as a way of re-orienting the development of Innovation and technology into business and education sector to curb the future challenges.
Keywords: Innovation science.; Technology.; Education.; Business.; Turbulent times.